Reducing Pre-Operative Anxiety in Major Surgery Patients (Laparatomy) Through Emotional Support and Deep Breathing Relaxation Therapy at Hospital X - Icha Anandita Dewi; Shindi Hapsari (Sean Institute, 2026)
Preoperative anxiety is a common psychological response among patients undergoing major surgery and may negatively affect physiological stability and surgical outcomes. This study aimed to examine the effectiveness of emotional support and deep breathing relaxation in reducing preoperative anxiety among major laparotomy patients at RSUD X. A quantitative quasi-experimental study with a one-group pretest–posttest design was conducted involving 10 patients selected through total sampling. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). The intervention, consisting of emotional support and deep breathing relaxation, was administered for 10–15 minutes before surgery. Data were analyzed using the Paired Sample t- test. The results demonstrated a significant reduction in anxiety levels following the intervention (p = 0.02). These findings indicate that emotional support and deep breathing relaxation are effective non-pharmacological nursing interventions for reducing preoperative anxiety and may improve patients’ psychological readiness before major surgery.